UNCOVERing the High-redshift AGN Population among Extreme UV Line Emitters - Helena Treiber; Jenny E. Greene; John R. Weaver; Tim B. Miller; Lukas J. Furtak; David J. Setton; Bingjie Wang; Anna de Graaff; Rachel Bezanson; Gabriel Brammer; Sam E. Cutler; Pratika Dayal; et al. (The Astrophysical Journal)
JWST has revealed diverse new populations of high-redshift ( z  ∼ 4–11) active galactic nuclei (AGNs) and extreme star-forming galaxies that challenge current photoionization models. In this paper, we use rest-frame UV emission-line diagnostics to identify AGN candidates and other exceptional ionizing sources, complementing previous studies predominantly focused on broad-line AGNs. From a parent sample of 205 z _spec  > 3 UNCOVER galaxies with NIRSpec/PRISM follow-up, we identify 12 galaxies with C IV , He II , and/or C III ] emission. Three of these galaxies also exhibit clear N III ] and/or N IV ] lines. Leveraging the combined rest-optical and UV coverage of PRISM, we limit the emission-line model space using the sample’s [O III ]/H β distribution, significantly decreasing the overlap between AGN and star formation models in the UV diagnostics. We then find that the five He II emitters are the strongest AGN candidates, with further support from two [Ne v ] detections and one X-ray detection from Chandra. Our Balmer line fits also reveal one new broad-line AGN at z = 6.87. We cannot robustly quantify the AGN fraction in this sample, but we note that close to 20% of M _*  > 2 × 10 ^9 M _⊙ parent sample galaxies are AGN candidates. The lower-mass line emitters, which are consistent with both AGN and star-forming photoionization models, have more compact sizes and higher specific star formation rates than the parent sample. Higher-resolution and deeper data on these UV line emitters should provide much stronger constraints on the obscured AGN fraction at z  > 3.